2019
DOI: 10.1177/1550059418817966
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Treatment Response in Pharmacological and Lifestyle Interventions Using Electroencephalography in ADHD: A Review

Abstract: Attention-deficit/hyperactivity disorder (ADHD) is a neurodevelopmental disorder characterized by inattention, hyperactivity, and/or impulsivity with associations to short- and long-term aversive life events. The exact etiology of the disorder is still unknown. ADHD is heterogeneous in symptomology and a single consistent, reliable biomarker has not been found. Quantitative electroencephalography (EEG) has been proposed as a potential way to differentiate those with ADHD from typically developing controls; how… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 97 publications
(152 reference statements)
0
20
0
Order By: Relevance
“…Hyperactivity, inattention and impulsivity in children has early on been suggested to be reflected in a cortical slowing of processing in frontal regions i.e., and increase in slow (theta, ~2–8 Hz) band activity in EEG recordings [170,171] reflecting decreased alertness possibly due to abnormal monoaminergic transmission in the corticocortical and corticostrital networks described below (but see also [172] for a review). The relative theta-to-beta (16–25 Hz) activity over midline electrodes (i.e., the theta/beta ratio, TBR) represents an FDA approved adjunct diagnostic tool for pediatric ADHD although it is associated with some controversy (see [173] for discussion and meta-analysis).…”
Section: The Neurophysiology Of Adhd and How Exercise May Exert Bementioning
confidence: 99%
“…Hyperactivity, inattention and impulsivity in children has early on been suggested to be reflected in a cortical slowing of processing in frontal regions i.e., and increase in slow (theta, ~2–8 Hz) band activity in EEG recordings [170,171] reflecting decreased alertness possibly due to abnormal monoaminergic transmission in the corticocortical and corticostrital networks described below (but see also [172] for a review). The relative theta-to-beta (16–25 Hz) activity over midline electrodes (i.e., the theta/beta ratio, TBR) represents an FDA approved adjunct diagnostic tool for pediatric ADHD although it is associated with some controversy (see [173] for discussion and meta-analysis).…”
Section: The Neurophysiology Of Adhd and How Exercise May Exert Bementioning
confidence: 99%
“…Brain source localization of the EEG signal of ADHD patients has created a new way for diagnosing and treatment of the disease. Some studies suggested the application of the quantitate EEG in the assessment of diversities in baseline spectral power profiles and pharmacological and nonpharmacological treatments which had effects on electrocortical activity [96]. Table II summarizes major studies and research concerning ADHD source localization.…”
Section: Diagnosis Of Brain Abnormalities Using Common Eeg Source Locmentioning
confidence: 99%
“…However, the identification of EEG subgroups may help to optimize treatments (stimulant and non-stimulant treatment, neurofeedback, exercise, and dietary intervention) and/or measure the response to them. Indeed, stimulant treatment was more efficient in the hypoarousal subgroup [for review, see Kirkland (72)] or unstable alertness (70) and was not efficient in ADHD patients with a slowed individual alpha peak frequency (73).…”
Section: Perspectives In Terms Of Evaluation Of Sleepiness With Eeg Cmentioning
confidence: 99%